Development and Validation of a Novel Histone Acetylation-Related Gene Signature for Predicting the Prognosis of Ovarian Cancer - Dai, Qinjin; Ye, Ying (Frontiers in Cell and Developmental Biology, 2022)
Abstract Histone acetylation is one of the most common epigenetic modifications, which plays an important role in tumorigenesis. However, the prognostic role of histone acetylation-regulators in ovarian cancer (OC) remains little known. We compared the expression levels of 40 histone acetylation-related genes between 379 OC samples and 88 normal ovarian tissues and identified 37 differently expressed genes (DEGs). We further explored the prognostic roles of these DEGs, and 8 genes were found to be correlated with overall survival (P < 0.1). In the training stage, an 8 gene‐based signature was conducted by the least absolute shrinkage and selector operator (LASSO) Cox regression. Patients in the training cohort were divided into two risk subgroups according to the risk score calculated by the 8-gene signature, and a notable difference of OS was found between the two subgroups (P < 0.001). The 8-gene risk model was then verified to have a well predictive role on OS in the external validation cohort. Combined with the clinical characteristics, the risk score was proved to be an independent risk factor for OS. In conclusion, the histone acetylation-based gene signature has a well predictive effect on the prognosis of OC and can potentially be applied for clinical treatments.